Politics and power in early medieval Europe : Alsace and the Frankish Realm, 600-1000 - Hummer, Hans J. (Cambridge studies in medieval life and thought, 2005)
Taking Alsace as its focus, this innovative study offers a unique snapshot of localised and centralised political structures in early medieval Europe. Providing a comprehensive exploration of the regional sources, it tracks the development and eventual demise of a distinctive political culture derived from networks of monasteries and kin-groups.